Spawning patterns provide further evidence for multiple stocks of sardine (Sardinops sagax) off eastern Australia. (20th July 2018) - Sexton, Stuart C.; Ward, Tim M.; Stewart, John; Swadling, Kerrie M.; Huveneers, Charlie
Abstract: Previous studies have suggested that sardine, Sardinops sagax, off eastern Australia spawns across its entire range when habitat conditions are suitable. However, recent studies have suggested that separate sub‐populations and spawning groups may occur in the region. Spawning patterns off eastern Australia were investigated using data collected during nine ichthyoplankton surveys conducted between 1997–2015, and adult reproductive data obtained from ad hoc commercial sampling off New South Wales (NSW). The egg surveys covered the known distribution of sardine off eastern Australia and included year‐round sampling in the northern and southern parts of this range. Egg distributions and analysis of gonadosomatic indices identified two spatio‐temporally separate spawning groups; one occurring off southern Queensland to northern NSW during late winter and early spring, and a smaller group off eastern Tasmania to southern NSW during summer. Most eggs were collected from waters 50–90 m deep, with sea surface temperatures of 18–23°C. Additive modelling indicated depth was the most significant factor driving selection of spawning habitat, followed by the interaction of month and latitude. Low egg densities were recorded in waters between 34–37°S, despite conditions within the ranges suitable for spawning. The presence of two spawning groups of sardine off eastern Australia supports recent findings that two sub‐populations occur in the region. Findings of this study will help to optimise the spatio‐temporal extent of future egg surveys and further confirm the need to coordinate future management of each sub‐population among relevant jurisdictions.